High-voltage electric discharge as pretreatment for efficient extraction of bioactive compounds from red onion peel. (October 2022) - Hejazi, Sina; Siahpoush, Vahid; Ostadrahimi, Alireza; Kafil Gazi Jahani, Behnam; Ghasempour, Zahra
Abstract: The outer skins of onions are rich in various functional compounds, and the extraction of phytonutrients is one of the most critical steps during their processing. The effects of the energy (12.5–50 J/mL) and the liquid/solid ratio (30–60) were investigated using a central composite design (CCD). It was observed that an increment in energy input caused a steep rise in total phenol content. On the other hand, as the L/S ratio increased, the anthocyanin content decreased dramatically. At lower L/S ratios, the DPPH scavenging activity peaked after increasing the energy input. Optimum conditions were determined as the energy input of 49.37 J/mL and the L/S ratio of 40. Scanning electron microscopy images demonstrated a severely ruptured cell wall structure during HVED extraction. The treated ROP extract completely prevented the growth of Pseudomonas aeruginosa colonies. The high extraction rate of total phenols and potent antibacterial activity highlight the excellent potential of HVED in extracting phytochemicals. Highlights: High-voltage electric discharge (HVED) is a new technique that enables green extraction. Compared with the control, almost twice as much bioactives were extracted via HVED pretreatment. HVED-treated extracts showed the greatest growth inhibitory effect against Pseudomonas aeruginosa . HVED possesses the potential to improve large-scale extraction processes.